2008
DOI: 10.3354/meps07539
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of coastal fish larvae as indicators of recent changes in ocean and climate conditions in the Oregon upwelling zone

Abstract: We examined ichthyoplankton sampled from 2 stations, 9 and 18 km offshore of Newport, Oregon, USA, over a decade of cruises every 2 wk from 1996 to 2005. The 10 most dominant taxa comprised approximately 87.3% of the total catch. Concentration of fish larvae was highest in January to March, whereas diversity peaked from March through May. Both overall diversity and density of larval fishes were relatively constant throughout the period of 1996 to 2003, with a dramatic decrease in these metrics since 2004, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…Doyle et al (2002) examined the spring and early summer ichthyoplankton assemblages in the NCC from Washington to northern California and found substantial latitudinal coherence in the species assemblages, with most of the spatial variability related to cross-shelf differences. Additionally, Auth (2008) found that the ichthyoplankton community between southern Oregon and central Washington (43.00-47.00°N) in May 2004-2006 was similar in terms of concentration, distribution, and community structure, while Auth (2011) also found no significant north-south concentration pattern for total larvae collected in May-October 2004-2009 between southcentral Oregon and southern Washington (44.00-46.67°N). Finally, the relationship between the larval community in this region and broad NCC basin-scale indices such as MEI, NOI, and PDO has been documented in several recent studies (Auth 2008, 2011, Brodeur et al 2008, Auth et al 2011.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Doyle et al (2002) examined the spring and early summer ichthyoplankton assemblages in the NCC from Washington to northern California and found substantial latitudinal coherence in the species assemblages, with most of the spatial variability related to cross-shelf differences. Additionally, Auth (2008) found that the ichthyoplankton community between southern Oregon and central Washington (43.00-47.00°N) in May 2004-2006 was similar in terms of concentration, distribution, and community structure, while Auth (2011) also found no significant north-south concentration pattern for total larvae collected in May-October 2004-2009 between southcentral Oregon and southern Washington (44.00-46.67°N). Finally, the relationship between the larval community in this region and broad NCC basin-scale indices such as MEI, NOI, and PDO has been documented in several recent studies (Auth 2008, 2011, Brodeur et al 2008, Auth et al 2011.…”
Section: Discussionmentioning
confidence: 96%
“…This may have led to fewer larvae surviving or a shift in their distribution off the shelf, potentially rendering them unavailable to juvenile salmon as prey. This delayed upwelling negatively affected larval fish growth and survival as well as seabird breeding success (Sydeman et al 2006, Auth 2008, Takahashi et al 2012. El Niño years may also be character ized by reduced or ineffective upwelling that has been shown to result in dramatic changes in the ichthyoplankton communities in the NCC (Brodeur et al 1985, Doyle 1995, Lenarz et al 1995.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations